Chemical and physical characteristics of Indo-Pacific Tarpon (Megalops cyprinoides) nugget with substitution of tapioca flour and Gracilaria sp. flour - Rizal Rifani; Irman Irawan; Seftylia Diachanty; Ita Zuraida; Septiana Sulistiawati (Universitas Teuku Umar, 2025)
Indo-Pacific Tarpon (Megalops cyprinoides) is one of the marine fish commodities found in East Kalimantan and North Kalimantan. One of the uses of Indo-Pacific fish meat is by processing it into nuggets. Fillers such as tapioca flour cause the texture of the nuggets to be too chewy and rather hard, so alternatives binders such as Gracilaria sp. flour are needed. The purpose of this study was to determine the effect of tapioca flour and Gracilaria sp. flour substitution on the physicochemical characteristics of bulan-bulan fish nuggets. This study used an experimental method with a Completely Randomized Design (CRD) with treatment R0 (20% tapioca flour); R1 (15% tapioca flour :5% Gracilaria sp. flour); R2 (10% tapioca flour:10% Gracilaria sp. flour); R3 (5% tapioca flour: 15% Gracilaria sp. flour); R4 (20% Gracilaria sp. flour) and repeated 3 times. The results of the ANOVA test showed that the substitution of tapioca and Gracilaria sp. flour had a significant effect (p<0.05) on moisture content, protein, fat, ash, carbohydrates, brightness (L*), redness (a*), yellowness (b*), degree of whiteness and EMC (Expressible Moisture Content). Nugget of bulan-bulan fish substituted with tapioca and Gracilaria sp. flour had a moisture content ranged from (51.89%-52.28%), ash (5.61-6.16%), fat (9.30%-11.29%), protein (32.72% -37.67%), carbohydrates (59.63%-55.77%), EMC (9.51%-25.26%). The results of the folding test Grade A (no cracks if folded in half a circle) and Grade B (cracked if folded in half a circle), with brightness (L*) (61.94-65.98), a* (4.62 - 4.33), b* (21.28 - 23.17) and whiteness (54,91%-56.37%). Based on chemical and physical characteristics, the R2 treatment was the best treatment in this study